Water Turbidity Monitoring System, Water Temperature and Fish Feed Using Arduino Mega 2560 Web-Based - Abdul Khayr; Ritzkal Ritzkal; Bayu Adhi Prakosa (Jurnal Mantik, 2020)
In daily life, fish that are kept in an aquarium must be aware of water turbidity, water temperature and feeding so that these fish need tools that can be adjusted continuously. As for the background of this writing is checking water turbidity, water temperature and feeding fish are still done manually, causing problems when fish keepers are busy or have to leave the house for a long time. The formulation of the problem of this research are (i) how to design and implement a monitoring system for water turbidity, water temperature and fish feed using the WEB-based Arduino Mega 2560 which can be scheduled based on time and (ii) how are the results of the monitoring system testing water turbidity, water temperature fish feed using WEB-based Arduino Mega 2560. By conducting 4 stages of research (i) Analysis of System Work and Requirements Analysis (ii) Design of Hardware Design, Schematic Design, Database Design, WEB Design, Network Design (iii) Hardware Implementation and Software Implementation (iv) Testing. The results of this study are a monitoring system for water turbidity, water temperature and fish feed according to a predetermined schedule with a monitoring system using the web. Water turbidity, water temperature and feeding are adjusted as needed. The servo will be active if the time on the real time clock (RTC) is the same as the schedule data variable that has been set.